Role of pancreatic ductal adenocarcinoma risk factors in intraductal papillary mucinous neoplasm progression - Gentiluomo, Manuel; Corradi, Chiara; Arcidiacono, Paolo Giorgio; Crippa, Stefano; Falconi, Massimo; Belfiori, Giulio; Farinella, Riccardo; Apadula, Laura; Lauri, Gaetano; Bina, Niccolò; Rizzato, Cosmeri; Canzian, Federico; et al. (Frontiers in Oncology, 2023)
Introduction: Pancreatic ductal adenocarcinoma (PDAC) is a lethal cancer due to late diagnosis, and lack of successful treatments. A possible strategy to reduce its death burden is prevention. Intraductal papillary mucinous neoplasms (IPMNs) are precursors of PDAC. It is difficult to estimate IPMN incidence because they are asymptomatic. Two recent studies reported pancreatic cysts in 3 and 13% of scanned subjects. The possibility of identifying a subgroup of IPMN patients with a higher probability of progression into cancer, could be instrumental in increasing the survival rate. In this study, genetic and non-genetic PDAC risk factors were tested in a group of IPMN patients under surveillance. Methods: A retrospective study was conducted on 354 IPMN patients enrolled by two Italian centres with an average follow-up of 64 months. Using DNA extracted from blood, collected at IPMN diagnosis, all patients were genotyped for 30 known PDAC risk loci. The polymorphisms were analysed individually and grouped in an unweighted polygenic score (PGS) in relation to IPMN progression. The ABO blood group and non-genetic PDAC risk factors were also analysed. IPMN progression was defined based on the development of worrisome features and/or high-risk stigmata during follow-up. Results: Two genetic variants (rs1517037, rs10094872), showed suggestive associations with an increment of IPMN progression. After correction for multiple testing, using the Bonferroni correction, none of the variants showed a statistically significant association. However, associations were observed for the non-genetic variables, such as smoking status, comparing heavy smokers with light smokers (HR = 3.81, 95% 1.43-10.09, P= 0.007), and obesity (HR=2.46, 95%CI 1.22-4.95, P= 0.012). Conclusion: In conclusion, this study is the first attempt to investigate the presence of shared genetic background between PDAC risk and IPMN progression, however, the results suggest that the 30 established PDAC susceptibility polymorphisms are not associated with clinical IPMN progression in a sample of 354 patients. On the other hand, we observed indications of cigarette smoking, and BMI involvement in IPMN progression, The biological mechanism that could link these two risk factors to progression, could be chronic inflammation, of which both smoking and obesity are strong promoters.